Circulating Memory T Follicular Helper Cells in Patients with Neuromyelitis Optica/Neuromyelitis Optica Spectrum Disorders - Xueli Fan; Yanfang Jiang; Jinming Han; Jingyao Liu; Yafen Wei; Xinmei Jiang; Tao Jin (Hindawi Limited, 2016)
Objective. This study aimed to examine the potential role of memory T follicular helper (Tfh) cells in patients with neuromyelitis optica/neuromyelitis optica spectrum disorders (NMO/NMOSD). Methods. The percentages of different subsets of circulating memory Tfh cells in 25 NMO/NMOSD patients before and after treatment as well as in 17 healthy controls were examined by flow cytometry. The levels of IL-21 and AQP4 Ab in plasma and CSF were measured by ELISA. Results. The percentages and numbers of circulating memory Tfh cells, ICOS+, CCR7−, CCR7−ICOS+, CCR7+, CCR7+ICOS+ memory Tfh cells, and the levels of IL-21 in plasma and CSF were significantly increased in NMO/NMOSD patients. The percentages of CCR7− and CCR7−ICOS+ memory Tfh cells were positively correlated with ARR, plasma IL-21, and AQP4 Ab levels. The percentages of CCR7+ and CCR7+ICOS+ memory Tfh cells were positively correlated with CSF white blood cell counts, proteins, and IL-21 levels. Treatment with corticosteroids significantly reduced the numbers of CCR7−ICOS+ and CCR7+ICOS+ memory Tfh cells as well as plasma IL-21 levels in patients with partial remission. Conclusions. Our findings indicate that circulating memory Tfh cells may participate in the relapse and development of NMO/NMOSD and may serve as a new therapeutic target.